PENGARUH RETURN ON ASSETS (ROA), RETURN ON EQUITY (ROE), DEBT TO EQUITY RATIO (DER), EARNING PER SHARE (EPS), DAN PRICE EARNING RATIO (PER) TERHADAP RETURN SAHAM - Ade Reza Bakhtiar; Saryadi Saryadi (Jurnal Ilmu Administrasi Bisnis, 2017)
One of the investor’s aims in investing on emiten is to get a return. To get a stock’s return, the loss risks cannot be denied, and it is affected by the stock’s price fluctuation that is cannot be determined. However, as the stocks exchange is rapidly developed, it does not mean that the risk limit cannot be decreased. The technical and fundamental analysis have become a solution for the investor to predict the stocks’ price. Specifically, this research discusses about the fundamental analysis by appraising the companies’ performance which is depicted on the companies’ financial report with ratio as a tool to analyze the financial report. By using the financial ratio, it can be seen and it can be an image for the investors about the good and bad images of the companies’ condition, so that it would be a basis for the investors for choosing the companies that have a higher return level than the loss risks. The aim of this research are too understand the influences of Return On Assets (ROA), Return On Equity (ROE), Debt to Equity Ratio (DER), Earning Per Share (EPS), and Price Earning Ratio (PER) toward Stock’s Return. The population in this research is the companies that are listed on the sub-sectored stocks in property and real estate during the period of 2012-2016. There are 22 companies that are matched with the following criteria as the research’s sample. The quantitative analysis use the classic assumptions’ test, coefficient correlation determination coefficient, simple regression, double regression, and significances test (uji t and F). The result from this research shows that Return on Assets (ROA) affects the stock’s return. Return on Equity (RO) affects the stock’s return. Debt to Equity Ratio (DER) is not affected the stock’s return. Earning Per Share (EPS) affects the stock’s return. Price Earning Ration (PER) affects the stock’s return. The dependent variable simultaneously influence the stock’s return. As a suggestion, there will be better if a company make a decision to efficient the budget in order to improve the profits, identify and group the assets that either have a potential or not which are used to support the companies’ operational procedure and to optimize the modal’s using.